Advances in Intelligent Information Hiding and Multimedia Signal Processing Proceedings of the Thirteenth International Conference on Intelligent Information Hiding and Multimedia Signal Processing, August, 12-15, 2017, Matsue, Shimane, Japan, Part I - Pan, Jeng-Shyang.; Tsai, Pei-Wei.; Watada, Junzo; Jain, Lakhmi C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume includes papers presented at IIH-MSP 2017, the 13th International Conference on Intelligent Information Hiding and Multimedia Signal Processing, held on 12-15 August 2017 in Matsue, Shimane, Japan. The conference covered topics ranging from information hiding and security, and multimedia signal processing and networking, to bio-inspired multimedia technologies and systems. This volume focuses on subjects related to multimedia security and applications, wearable computing, Internet of Things (IoT) privacy and information security, biomedical system design and applications, emerging techniques and applications, soft computing and applications, applications of image encoding and rendering, and information hiding and its criteria. Updated with the latest research outcomes and findings, the papers presented appeal to researchers and students in the corresponding fields.
A Survey of Reversible Data Hiding Schemes Based on Two-dimensional Histogram Modification -- Steganographic Image Hiding Schemes Based on Edge Detection -- A New Data Hiding Strategy Based on Pixel-Value-Differencing Method -- Data Hiding Scheme Based on Regular Octagon-shaped Shells -- A Web Page Watermarking Method using Hybrid Watermark Hiding Strategy -- Integrated Health Check Report Analysis and Tracking Platform -- A Study of the Multi-Organization Integrated Electronic Attendance System -- A Content Analysis of Mobile Learning on Constructivism Theory -- An Independence Mechanism Design for the Software Defined Device -- An Ontology-based Herb Therapy Recommendation for Respiration System -- Robust Optimal Control Technology for Multimedia Signal Processing Applications -- Implementation of an eBook Reader System with the Features of Emotion Sensing and Robot Control -- On the Automatic Construction of Knowledge-Map from Handouts for MOOC Courses -- Automated Music Composition Using HeartRate Emotion Data -- Inter-Vehicle Media Distribution for Driving Safety -- High-capacity ECG Steganography with Smart Offset Coefficients -- An Automatic People Counter in Stores Using a Low-cost IoT Sensing Platform -- Determination of Coefficient of Thermal Expansion in High Power GaN-based Light-emitting Diodes via Optical Coherent Tomography -- Compression-efficient Reversible Data Hiding in Zero Quantized Coefficients of JPEG Images -- On the Security of a Certificateless Public Key Encryption with Keyword Search -- DCT-based Compressed Image with Reversibility using Modified Quantization -- Studying the Influence of Tourism Flow on Foreign Exchange Rate by IABC and Time-Series Models -- Short-term Forecasting on Technology Industry Stocks Return Indices by Swarm Intelligence and Time-Series Models -- Image Segmentation for Lung Lesions using Ant Colony Optimization Classifier in Chest CT -- SURF Algorithm-based Panoramic Image Mosaic Application -- Simulation of Long-distance Aerial Transmissions for Robust Audio Data Hiding -- Variable-Length Key Implementation Based on Complex Network WSN Clustering -- An Infrared Small Target Detection Method based on Block Compressed Sensing -- An Encryption Algorithm for ROI Images.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Multimedia systems; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Multimedia Information Systems